Squamous cell carcinoma of the oral cavity with metastasis to the urinary bladder - Tanmaya Goel; Sreedhar Reddy; Joseph Thomas; Shveta Garg (Indian Journal of Urology, 2006)
Squamous cell carcinoma (SCC) of the oral cavity with metastasis to the urinary bladder is an unreported phenomenon. There are a few reports of transitional cell carcinoma of the bladder metastasizing to the oral cavity, though very rare. Thus, the possibility should always be borne in mind.